Biometric Voting System using LABVIEW - P. Vishnu Kumar; Y. Pavani; P. Nasreen; M. Pratyusha; G. Mounika Bai (Journal of Power Electronics and Devices, 2022)
There are various methods to avoid fraudulence in the voting system. The main aim of the biometric voting system using LABVIEW is to improve the Indian voting system. By implementing the Bio-metric process, we can make the polling process more secure and efficient than the existing one. Every resident of India has a right to cast a vote and to utilize this right the election process should happen fairly and efficient. The election commission of India has a prime responsibility to implement the most efficient methods for voting. The political race commission of India has various sorts of casting a ballot framework; for example, emit expressive dance paper technique, and presently Electronic Voting Machine ( EVM’s) and Voter Verified Paper Audit Trail (VVPAT) casting ballot machines. The ongoing democratic framework has EVMs which can be hacked without any problem. There are many methods adopted to avoid malpractices. Here we’re using Global System for Mobile communication (GSM) module for sending messages to the citizens who cast their vote, that “your vote cast successfully, thank you," and also send alert notifications to assigned police in charge near the polling booth if the voter tries to reattempt to cast a vote. The person at the station must put their finger on the digits so that the veteran can get the digit identification card. This data is sent to the LABVIEW Control Unit for verification. The LABVIEW control unit receives and compares data from the reader with data already collected during voting registration. Individuals will be allowed to vote if information related to fingerprint information is contained in the database. Individual votes are prohibited unless a warning message is displayed in the dialog box.